2000
DOI: 10.1053/eupc.2000.0120
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of autonomic tone in patients below 50 years of age with unexplained cerebral infarction: relation to atrial vulnerability

Abstract: The long-term autonomic tone parameters of young patients presenting with a history of unexplained cerebral infarction are similar to those of healthy control subjects and are not correlated with atrial vulnerability parameters or atrial fibrillation inducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
1
1
Order By: Relevance
“…It has been suggested that this may induce episodes of paroxysmal atrial fibrillation, and even a tendency toward thromboembolism. 15 We did not find any association between HRV and admissions for atrial fibrillation. Even so, admissions for atrial fibrillation most likely only compose a small part of the total burden of atrial fibrillation.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…It has been suggested that this may induce episodes of paroxysmal atrial fibrillation, and even a tendency toward thromboembolism. 15 We did not find any association between HRV and admissions for atrial fibrillation. Even so, admissions for atrial fibrillation most likely only compose a small part of the total burden of atrial fibrillation.…”
Section: Discussioncontrasting
confidence: 53%
“…13,14 Stroke survivors have impaired function of the autonomic nervous system, and disturbances in sympathovagal balance may predict survival after the acute phase of stroke. 15,16 Survival after stroke correlates with reduced HRV. 16,17 An autonomic imbalance and reduced HRV have been identified prior to paroxysms of atrial fibrillation in some studies.…”
mentioning
confidence: 99%